(NmYSLI O REVISSUREs (NMETODIKAs - (Nw(B. (Ng(B. (NsAHNOWSKIJ s ((NsANKT(B-(NPETERBURGs (NlANXs (NpLANETA MUZYKIs)
(NdANNAQ KNIGA POSWQ]ENA PROBLEMAM REVISSURY(B, (NTWOR^ESKIM WOPROSAM(B, (NTAKIM KAK SCENI^ESKIJ STILX(B, (NRITM(B, (NKOMPOZICIQ(B, (NPROBLEMA VANRA W SPEKTAKLE(B, (NA TAKVE SCENI^ESKAQ USLOWNOSTX(B,s
Keywords: (NmETODIKAs